Foregrounding peer versus parental effects in adolescent emotional development - Undari Ramadhani; Zirmansyah Zirmansyah; Achmad Ushuluddin (SCHOULID: Indonesian Journal of School Counseling, 2026)
Adolescence is a critical developmental stage in which emotional intelligence plays a fundamental role in psychological well-being, interpersonal relationships, and academic adjustment. This study examined the influence of parent–child communication and peer friendship quality on the emotional intelligence of students at Senior High School X Jakarta. A quantitative explanatory study with a cross-sectional survey design was conducted involving 73 students selected through total sampling. Parent–child communication, peer friendship quality, and emotional intelligence were measured using standardized questionnaires. The data were analyzed using multiple linear regression with IBM SPSS Statistics. The results of the partial (t-test) analysis indicated that parent–child communication did not significantly predict emotional intelligence, whereas peer friendship quality had a significant positive effect. Furthermore, the simultaneous (F-test) analysis demonstrated that parent–child communication and peer friendship quality jointly exerted a statistically significant influence on emotional intelligence (F = 5.112, p = 0.008), explaining 12.7% of the variance in emotional intelligence (R² = 0.127). These findings indicate that adolescents' emotional intelligence is influenced by the combined contribution of family and peer environments, with peer friendship quality emerging as the stronger predictor. The findings contribute to the understanding of adolescent emotional development by highlighting the importance of examining multiple social contexts simultaneously and provide empirical evidence to support the development of school-based social–emotional learning initiatives aimed at strengthening students' emotional competence.